(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2024)
The Batanghari River, as the primary water source for the Jambi City Water Utility (PDAM), has been subjected to pollution caused by anthropogenic activities, particularly those stemming from industrial, agricultural, and domestic sectors. Concentrations of heavy metals such as mercury (Hg), cadmium (Cd), copper (Cu), lead (Pb), and zinc (Zn) have been detected at levels exceeding the limits established by Government Regulation No. 22 of 2021. This research aimed to mitigate the presence of heavy metals in the Batanghari River through adsorption techniques utilizing Susuh kura snail shells as a natural adsorbent. The characterization of the adsorbent was conducted using Scanning Electron Microscopy (SEM) to analyze its morphology and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) to assess the heavy metal content in the river water. The snail shells were treated under varying thermal conditions: uncalcined, and calcined at 500 °C and 700 °C. The results indicated that calcium oxide (CaO) derived from shells calcined at 500 °C exhibited the highest adsorption efficiency, achieving up to 80% reduction in heavy metal concentrations. These findings suggest that waste snail shells possess significant potential as a low-cost, eco-friendly natural adsorbent for addressing heavy metal contamination in aquatic environments, offering a sustainable solution for water treatment.